The estimated tax revenue resulting in film industry support program - Holcová, Lucie (2016)
The goal of this Bachelor´s thesis is to estimate the yield of collected taxes, local taxes and rents resulting in film incentive and flowing into public budgets in the Czech Republic. The thesis describes the relationship of the state and film industry before and after 1989, and the system of film incentives. The possibility of estimation and the estimation itself, which is processed for the currently shooting film Interlude in Prague, the film incentive is allocated in the amount of 37,961,408 CZK. My estimation of the revenue is in the amount of 28,129,795 CZK.